Reciprocal Relationships Between Moral Competence and Externalizing Behavior in Junior Secondary Students: A Longitudinal Study in Hong Kong - Shek, Daniel T. L.; Zhu, Xiaoqin (Frontiers in Psychology, 2019)
Defining moral competence using a virtue approach, this longitudinal study examined the prospective relationships between moral competence and externalizing behavior indexed by delinquency and intention to engage in problem behavior in a large and representative sample of Hong Kong Chinese adolescents. Starting from the 2009–2010 academic year, Grade 7 students in 28 randomly selected secondary schools in Hong Kong were invited to join a longitudinal study, which surveyed participating students annually during the high school years. The current study used data collected in the first three years (Wave 1 to Wave 3) across junior secondary school stage (Grade 7 to Grade 9) with a sample of 3,328 students (Age = 12.59 ± .74 years and 52.1% boys at Wave 1). Cross-lagged panel path analyses were conducted to compare four models involving different hypothesized patterns of relationships between moral competence and externalizing behavior. Results revealed that the reciprocal effects model best fit the data, supporting reciprocal causal relationships between moral competence and externalizing behavior measures. Specifically, a higher level of moral competence significantly predicted a lower level of delinquency and problem behavioral intention over time. At the same time, a higher level of externalizing behavior also significantly predicted a lower level of moral competence one year later. As the magnitudes of the significant findings were not high, replications in different Chinese communities are needed. Nevertheless, the present findings provide important theoretical insights on how moral competence and externalizing behavior in adolescents are associated with each other. Practically speaking, the findings suggest that it is promising to reduce adolescent externalizing behavior by promoting their virtues through moral education programs, and guiding adolescents to behave in a good manner would help promote the development of their virtues.